2014
DOI: 10.1371/journal.pone.0086019
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Rat Pancreas Reveals Altered Expression of Alox15 and Regenerating Islet-Derived Genes in Response to Iron Deficiency and Overload

Abstract: It is well known that iron overload can result in pancreatic iron deposition, beta-cell destruction, and diabetes in humans. Recent studies in animals have extended the link between iron status and pancreatic function by showing that iron depletion confers protection against beta-cell dysfunction and diabetes. The aim of the present study was to identify genes in the pancreas that are differentially expressed in response to iron deficiency or overload. Weanling male Sprague-Dawley rats (n = 6/group) were fed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Other investigators have measured growth and Hb levels in rodents fed high-iron diets [ 36 38 ], including some studies that have used weanling SD rats [ 39 , 40 ]. In general, most studies documented decrements in body weight after high-iron feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have measured growth and Hb levels in rodents fed high-iron diets [ 36 38 ], including some studies that have used weanling SD rats [ 39 , 40 ]. In general, most studies documented decrements in body weight after high-iron feeding.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanistic explanation for altered growth rates was, however, not provided. A few studies also measured Hb levels after high-iron feeding and showed no changes [ 36 , 40 ] or an increase [ 39 ]. Differences between these previous studies and the current investigation could relate to the diets used, the length of feeding, the specific strain of mouse or rat used, and/or to rodent housing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the work of Choi et al, [ 40 ], who used subtractive hybridization and DNA sequencing of whole pancreas to demonstrate that Reg3α changes the expression level of islet marker genes, including NEUROD, NKX2.2, PAX4, and PAX6. Furthermore, Reg expression may serve as a biomarker for iron-related pancreatic stress, as iron changes may contribute to diabetes development through up-regulation of Alox15 [ 41 ]. Overall, RegIIIα may represent a novel therapeutic target to modulate beta cell function, survival and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Another micronutrient of relevance to T2D is iron, because both iron overload and deficiency have been linked to impaired pancreatic function and glucose homeostasis. In a microarray analysis of rat pancreas with either iron deficiency or iron overload, genes involved in lipid transport and encoding pancreatitis-associated proteins were found to be significantly affected in both conditions, thus supporting their involvement in pancreatic functions and T2D (Coffey et al 2014 ). These micronutrient studies, therefore, also point to a role of lipid metabolism/transport as a shared mechanism through which nutrients influence T2D.…”
Section: Nutritranscriptomics In T2dmentioning
confidence: 76%